2014
DOI: 10.1038/srep07447
|View full text |Cite
|
Sign up to set email alerts
|

Polarity continuation and frustration in ZnSe nanospirals

Abstract: ZnSe nanospirals including structures with polarity continuation and polarity frustration are simultaneously observed at atomic resolution. Through careful analysis of polarity within each dumbbell based on aberration-corrected high-angle annular-dark-field imaging, polarity continuation across parallel polytype interfaces as well as the surrounding Z-shape faulted dipoles is verified. Moreover, polarity frustration across regions with different stacking sequence, which would lead to accumulations of boundary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…As evident from the normal WZ ZnSe shown in Figure a, the projected orientation of the Zn–Se bonds in the horizontal direction are reversed in alternating rows along the c -axis (indicated by red and green arrows). This orientation indicates that the spontaneous polarization is aligned with the c -direction, without a component in the ab plane, and corresponds to its polarized space group P 63 mc . , In our case, however, we observe an unusual symmetry-breaking structure and polarization phenomenon with the WZ ZnSe NCs. Figure b is the HAADF image of a typical WZ ZnSe particle that contains defective segments.…”
contrasting
confidence: 42%
See 1 more Smart Citation
“…As evident from the normal WZ ZnSe shown in Figure a, the projected orientation of the Zn–Se bonds in the horizontal direction are reversed in alternating rows along the c -axis (indicated by red and green arrows). This orientation indicates that the spontaneous polarization is aligned with the c -direction, without a component in the ab plane, and corresponds to its polarized space group P 63 mc . , In our case, however, we observe an unusual symmetry-breaking structure and polarization phenomenon with the WZ ZnSe NCs. Figure b is the HAADF image of a typical WZ ZnSe particle that contains defective segments.…”
contrasting
confidence: 42%
“…As a typical representative of II–VI semiconductor NCs, ZnSe possesses structures that include zincblende (ZB), with cubic stacking in the [111] direction, and wurtzite (WZ), with hexagonal stacking in the [0001] direction. ZB ZnSe is thermodynamically stable, whereas WZ ZnSe is metastable. In comparison with ZB ZnSe, WZ ZnSe is difficult to prepare under mild reaction conditions. , Furthermore, the controlled growth of WZ ZnSe NCs with alternating Zn and Se atom arrangements leads to a localized excess of charge, which is due to the polarization associated with symmetry-breaking structures. ,, The accumulation of charge in the WZ ZnSe structure can also affect the electron–hole recombination statistics, which may result in new properties. , Here, we propose WZ ZnSe as an ideal model to investigate the relationship between the WZ ZnSe structure and its ECL behavior.…”
mentioning
confidence: 99%
“…The HAADF–STEM image intensity directly scales with the atomic number Z giving Z contrast . In previous studies, the aberration‐corrected HAADF–STEM technique has been applied to characterization of local faulted structures as well as analysis of related structure–property relations at atomic resolution. Figure c is HAADF–STEM image of a small piece of K x WO 3 nanosheet with growth direction along [0001].…”
Section: Resultsmentioning
confidence: 99%
“…found that wurtzite ZnSe nanocrystals possess defective segments that break the translational symmetry of the crystal, as illustrated by aberration‐corrected high‐angle annular‐dark‐field (HAADF) images of wurtzite ZnSe nanocrystals in Figure 14. Such symmetry‐breaking defects induce local charge imbalances within the material, and result in novel optical properties [122,124] . Zinc blende ZnSe nanocrystals also displayed symmetry‐breaking defects, although electron holography experiments revealed that the net local charges in defective segments of ZnSe nanocrystals were greater in the wurtzite phase than in the zinc blende phase [122] …”
Section: Properties and Applications Of Semiconductor Nanocrystals Wimentioning
confidence: 99%